Collaborative interfacial shear capacity of adhesive bonding and novel shooting nail for steel plate strengthening concrete structures - Mingxue Xu; Lei Ren; Zheng Shi; Xiaogang Liu (Scientific Reports)
Abstract Shooting nail is a novel fastening approach for the reinforcement of concrete bridges and building structures using bonding steel plates, offering enhanced construction efficiency compared to traditional chemical anchor bolts. In addition, it may provide additional collaborative interfacial shear capacity contribution with adhesive bonding, but relative research is limited. To comprehensively explore the interfacial shear capacity of steel plate-concrete with adhesive bonding and shooting nail fastening, experimental investigations were first conducted. Afterward, FEA was utilized to investigate the influencing parameters on the collaborative contribution of adhesive bonding and shooting nails to interfacial shear capacity, including concrete strength, steel plate thickness, and nail spacing. On these bases, theoretical analysis of the additional interfacial shear contribution of shooting nails to steel place-concrete interface was conducted. Finally, based on the calculation formula of interfacial shear capacity of steel plate-concrete adhesive bonding, a new theoretical calculation approach of interfacial shear capacity was provided, considering the contribution of both adhesive bonding and shooting nail fastening.